Bone disease in diabetes: another manifestation of microvascular disease?. Issue 10 (October 2017) - Shanbhogue, Vikram V; Hansen, Stinus; Frost, Morten; Brixen, Kim; Hermann, Anne P
Summary: Type 1 and type 2 diabetes are generally accepted to be associated with increased bone fracture risk. However, the pathophysiological mechanisms of diabetic bone disease are poorly understood, and whether the associated increased skeletal fragility is a comorbidity or a complication of diabetes remains under debate. Although there is some indication of a direct deleterious effect of microangiopathy on bone, the evidence is open to question, and whether diabetic osteopathy can be classified as a chronic, microvascular complication of diabetes remains uncertain. Here, we review the current knowledge of potential contributory factors to diabetic bone disease, particularly the association between diabetic microangiopathy and bone mineral density, bone structure, and bone turnover. Additionally, we discuss and propose a pathophysiological model of the effects of diabetic microvascular disease on bone, and examine the progression of bone disease alongside the evolution of diabetes.